Manajemen Pengelolaan dan Pengembangan pada UMKM Kuliner Pempek Dapur Bunda - Maulana, Fakhry Reza (Green Publisher Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a strategic role in Indonesia's economy, but face various challenges in business management and development. This study aims to analyze the development strategy of Pempek Dapur Bunda culinary MSME through a SWOT analysis approach. The research method uses a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation of 11 informants consisting of business owners, employees, and customers. The SWOT analysis results show that Pempek Dapur Bunda is in quadrant I with IFAS score of 3.665 and EFAS score of 3.275, indicating a strategic position to implement aggressive growth strategies. The main strengths lie in customer loyalty, product quality, and reliable human resources, while weaknesses are found in fluctuating financial conditions and dependence on digital platforms. The greatest opportunities come from the development of social media and e-commerce, while the main threats are relatively expensive raw material prices and unstable economy. Recommended strategies include improving HR quality in technology, product innovation, and strengthening cooperation with the government.